Seismic and progressive collapse assessment of sideplate moment connection system - Faridmehr, Iman (Techno-Press, 2015)
The performance of a newly generated steel connection known as SidePlateTM moment connection for seismic loading and progressive collapse phenomenon has been investigated in this paper. The seismic evaluation portion of the study included a thorough study on of interstory drift angles and flexural strengths based on 2010 AISC Seismic Provisions while the acceptance criteria provided in UFC 4-023-03 guideline to resist progressive collapse must be satisfied by the rotational capacity of the connections. The results showed that the SidePlate moment connection was capable of attaining adequate rotational capacity and developing full inelastic capacity of the connecting beam. Moreover, the proposed connection demonstrated an exceptional performance for keeping away the plastic hinges from the connection and exceeding interstory drift angle of 0.06 rad with no fracture developments in beam flange groove-welded joints. The test results indicated that this type of connection had strength, stiffness and ductility to be categorized as a rigid, full-strength and ductile connection.